Evidence for Noachian flood volcanism in Noachis Terra, Mars, and the possible role of Hellas impact basin tectonics. Issue 5 (28th May 2013) - Rogers, A. D.; Nazarian, A. H.
Abstract : [1] Spectral and imaging data sets from Mars Reconnaissance Orbiter and Mars Odyssey, as well as spectral and topographic data from Mars Global Surveyor, are used to understand the origin of in‐place rock units found in the intercrater plains and Hellas circumferential graben floors of Noachis Terra, Mars. The rocky units are interpreted as effusive volcanic plains on the basis of broad areal extent, structural competence, association with topographic lows, distinct mineralogy from regolith, and lack of sedimentary textures or minerals associated with aqueous processes. Some rocky expanses contain at least two compositionally distinct units. The relatively light‐toned unit exhibits a higher plagioclase/pyroxene ratio than the lower, dark‐toned unit. Both units exhibit ~10% olivine enrichment compared to surrounding regolith. These units are heavily degraded and exhibit crater model ages between ~3.80 and 4.0 Ga, making these some of the oldest preserved volcanic plains accessible by remote sensing. They are found in association with Hellas ring structures, where the westward extent of these rocky units is limited to the outermost ring structure. Fracturing associated with the Hellas impact may have enabled magmas to ascend from the base of the crust in the circum‐Hellas region. Identification of these units as volcanic materials extends previous estimates for volume of outgassed volatiles. Though the estimated volcanic volume increase is minor, the local effects could have been significant. The role of multi‐ring impact basins in providing a spatial control on Martian highlands volcanism and subsurface mineralization may have been underestimated in the past. Key Points: Bedrock units in Noachis Terra contain two igneous lithologies and are 3.9 Ga Units probably volcanic and are spatially associated with Hellas ring structures Hellas fracturing and tectonics enabled magma ascent from base of crust